1993
DOI: 10.1007/bf00418777
|View full text |Cite
|
Sign up to set email alerts
|

Spatial direct numerical simulation of boundary-layer transition mechanisms: Validation of PSE theory

Abstract: Abstract. A study of instabilities in incompressible boundary-layer ow on a at plate is conducted by spatial direct numerical simulation DNS of the Navier-Stokes equations. Here, the DNS results are used to critically evaluate the results obtained using parabolized stability equations PSE theory and to study mechanisms associated with breakdown from laminar to turbulent o w. Three test cases are considered: two-dimensional TollmienSchlichting wave propagation, subharmonic instability breakdown, and oblique-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(66 citation statements)
references
References 40 publications
(39 reference statements)
8
58
0
Order By: Relevance
“…The results by the NavierStokes solver and by the parabolic stability equation solver agree remarkably well. This corresponds to the good agreement between the Navier-Stokes solver and the parabolic stability equation solver reported for the Blasius boundary layer mentioned above Bertolotti et al (1992); Joslin et al (1993). The results by the Orr-Sommerfeld solver on the other hand display an earlier growth of the Tollmien-Schlichting wave compared to the other two solvers.…”
Section: Linear Stability Of the Boundary Layer Flow Under A Solitarysupporting
confidence: 77%
See 1 more Smart Citation
“…The results by the NavierStokes solver and by the parabolic stability equation solver agree remarkably well. This corresponds to the good agreement between the Navier-Stokes solver and the parabolic stability equation solver reported for the Blasius boundary layer mentioned above Bertolotti et al (1992); Joslin et al (1993). The results by the Orr-Sommerfeld solver on the other hand display an earlier growth of the Tollmien-Schlichting wave compared to the other two solvers.…”
Section: Linear Stability Of the Boundary Layer Flow Under A Solitarysupporting
confidence: 77%
“…As the amplitude of the perturbation is considered small, the parabolic stability equation solver and the Navier-Stokes solver are expected to produce similar results, since they both contain all the essential physics of the problem. This has been observed by Bertolotti et al (1992) and Joslin et al (1993) in their stability analysis of the Blasius boundary layer. Figure 10 shows three plots for the case = 0.4 and δ = 8 · 10 −4 .…”
Section: Linear Stability Of the Boundary Layer Flow Under A Solitarysupporting
confidence: 54%
“…Implicit Crank-Nicolson time-advancement is used for the wallnormal di usion terms and a three-stage Runge-Kutta scheme for the remaining terms. A code validation study was previously performed by Joslin et al 1992Joslin et al , 1993 .…”
Section: Methodsmentioning
confidence: 99%
“…A comparison between the PSE and DNS schemes had previously been considered by Joslin et al (21) who found excellent agreement between the two methods for the propagation of two-dimensional T-S waves on a semi-infinite flat plate. However, unlike Joslin et al (21) the PSE method of (19) considered in this paper allows the comparison of T-S wave streamwise velocity amplitudes rather than just growth rates.…”
Section: Introductionmentioning
confidence: 95%